Торгівельно-економічне співробітництво між Росією і Францією на сучасному етапі - Побірченко, В.В.; Семенова, Ю.А. (Культура народов Причерноморья, 2014)
У статті розглянуті актуальні аспекти торгівельно-економічного співробітництва між
Росією і Францією. Охарактеризовано потенціал співпраці. Виділено перспективні напрямки, в тому
числі, співпраця в оборонній промисловості; партнерство і стратегічні міжфірмові альянси в
авіаційної, ракетно-космічної та атомної промисловості; партнерство в реалізації
високотехнологічних проектів та угод на ринках третіх країн. Зроблено висновок про взаємний інтерес
російських інноваційних кластерів і французьких полюсів конкурентоспроможності, в здійсненні планів
розвитку співробітництва між ними на основі чітко сформульованих рамок і пріоритетів такої
співпраці за підтримки національних урядів.
Ключові слова: торгівельне співробітництво, економічне співробітництво, конкурентоспроможність,
кластер, інновації, альянс. В статье рассмотрены актуальные аспекты торгово-экономического сотрудничества
между Россией и Францией. Охарактеризован потенциал сотрудничества. Выделены перспективные
направления, в том числе, сотрудничество в оборонной промышленности; партнерство и
стратегические межфирменные альянсы в авиационной, ракетно-космической и атомной
промышленности; партнерство в реализации высокотехнологичных проектов и сделок на рынках
третьих стран. Сделан вывод о взаимном интересе российских инновационных кластеров и французских
полюсов конкурентоспособности, в осуществлении планов развития сотрудничества между ними на
основе четко сформулированных рамок и приоритетов такого сотрудничества при поддержке
национальных правительств. In recent years, Russian-French cooperation in science and technology, investment and production
areas rapidly expanded. By 2014, the country moved from a simple supplier and buyer relationship to a strategic
partnership in which each of the parties to benefit from the experience of others in the process of implementing
large-scale joint industrial projects. As a result of favorable hallmark of Russia's relations with France was the
high concentration of joint projects in high-tech sectors: nuclear power, aerospace and medicine, and other
high-tech sectors, including in the framework of regional cooperation. Modern trade and economic relations
between Russia and France have a number of important features: 1) they have a more balanced partnership by
industry than with other countries of the European Union; 2) demonstrate unusually high for developed
countries concentration range of bilateral relations, including the French investments in the Russian economy,
high-tech, knowledge-intensive sectors; 3) shows an example of forming a deep partnership and inter-firm
alliances in strategically important Russian industries - aviation, space, missile, nuclear, as well as
unprecedented for a group of developed countries, the level of cooperation in the defense industry. The
complementary nature of economies, particularly in science and technology between the two countries, is able to
ensure the transition of the Russian-French relations, as the normalization of the political situation in the phase
of full-scale strategic partnership, building on innovation. This will contribute to the mutual interest of the
Russian innovation clusters and French poles of competitiveness, and the implementation of development plans
for cooperation between them on the basis of clearly defined scope and priorities of this cooperation, with the
support of national governments. The main task of further development of bilateral relations is the phased
implementation of an enhanced, task-oriented model of modernization of Russian-French economic cooperation,
based on the intensification of technical, scientific and technological exchange, industrial and technological
cooperation in knowledge-intensive industries, the creation of strategic alliances, inter-firm to achieve the
benefits of the global market.